Effectiveness of face masks for the population - Santarsiero, A.; Giustini, M.; Quadrini, F.; D'Alessandro, D.; Fara, G. M. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Health authorities and organizations consider non-medical face masks as an additional passive means to prevent virus diffusion. Communication strategies disseminate information among the population that such masks are essential for mitigating virus diffusion. However, scientific studies are not conclusive in showing the undisputed filtration efficiency of fabric/cloth facial masks (both commercial and homemade).Objectives. This study examines scientific data about the effectiveness of face masks before and during the COVID-19 emergency. Present trends in the making of commercial and homemade fabric/cloth face masks are also examined. Methods. Statistical data of published studies are analyzed and compared. Main considerations and suggestions are also extracted and discussed. Current approaches are examined for assessing the characteristics and effectiveness of fabric/cloth commercial and homemade face masks intended for the population. Results. Conflicting data exist as to whether non-medical masks have a protective effect from the spread of respiratory viruses. Both medical masks (MDs) and respiratory personal protection equipment (PPE) show a given effectiveness value. Conclusion. Concerning commercial and homemade fabric/cloth masks, giving general indications on the choice of materials and their assemblage is difficult as it is not possible to assess the effectiveness of the filter media with respect to the kind of multiphase fluid that may be emitted upon breathing, sneezing, or coughing under different environmental conditions. This is particularly important because airflow rate, temperature, humidity, and duration of use will affect the performance of filter media. Moreover, while a mask may have excellent filter media, droplets may leak into the face-piece unless there is an adequate facial seal. In the presence of leaks, any type of mask may actually offer less protection independently of its nominal filtering effìciency.